Studies of Zn(II) Ions Adsorption By Rice Husks Digested With Nitric Acid - Singgar, Diana (Universiti Teknologi Petronas, 2005)
Rice husks are one of the agro residues which are available from mills in relatively dry form. It is a carbonaceous material and abundantly available especially in Malaysia. Therefore it is an innovative step to convert this abundantly renewable source into fully utilization. This particular research studies will demonstrate the adsorption capacity of Zn(II) ions in solution using activated carbon produced from rice husk. The adsorption capacity of activated carbon is not only determined by their physical or porous structure but also strongly influenced by the chemical structure of their surface. The usage of nitric acid is imposed to oxidize the rice husk hence extended its surface acidity. Surface acidity is categorized as the chemical structure that influences the carbon interaction with polar and non-polar adsorbates, which is, in this case is Zn(II) ion. Specifically, there are two main experiment to be conducted prior to the research studies which are; formation of activated carbon under the various experimental condition and the analytical studies of the adsorption capacity using Atomic Absorption Spectrophotometer (AAS). Carbons which have equal surface area but prepared by different methods or given different activation treatments show markedly different adsorption characteristics. This particular research project will demonstrate the effect of three variations of experimental conditions which are; weight ratio of Nitric acid to rice husks, shaker speed and contact time and finally carbonization time. From the experiment, it was found that the maximum yield of activated carbon was obtained from rice husks subjected to acid digestion of weight ratio of 2, carbonization period of 0.5 hours and final heat temperature of 500°C. As for the adsorption properties, the rice husks subjected to treatment at the weight ratio of 2, carbonization period of 3 hours and temperature of 500°C displayed the best adsorption tendencytowards Zn(II) ions.